Financial development, institutional quality, and income inequality: comparative analysis between developed and developing countries - Cheah, Siew Pong (2022)
Reducing income inequality to a sustainable degree is of utmost importance, as extremely unequal income distribution is harmful to the social and economic wellbeing of any country. Therefore, governments and national leaders were committing or committed to reducing income inequality in their borders, and two of the most recognizable collective efforts are the Millennium Development Goals (MDGs, 2000 to 2015) and the succeeding Sustainable Development Goals (SDGs, 2015 to 2030). However, even after the participating members and organizations have put in enormous efforts and resources, there is, at best, limited achievement in reducing income inequality through the MDGs according to the World Gini index. One of the reasons behind this failure is that majority of the countries focused mainly on a progressive tax system to redistribute income while neglecting the fact that income inequality is multi-faceted. Likewise, this study questions on the potential of channels other than the fiscal taxation approach, namely the financial channel and the institutional channel, as effective alternatives in reducing income inequality in the context of developed and developing countries. Specifically, this study attempts to (i) investigate the roles of financial development and institutional quality in reducing income inequality, (ii) examine the potential interactive role of institutions and financial development in the inequality-finance-institution nexus, and (iii) examine the role of income inequality in endogenously determining institutional quality. Methodological wise, this study employs the System GMM technique on analyzing the panel datasets of 36 developed economies and 62 developing countries over the period from 1996 to 2015. The results revealed the following major findings. First, both financial development and institutional quality played an important role in determining income inequality in both advanced and developing countries. Stronger institutions exert a linear and negative effect on income inequality, and this negative effect holds across all aspects of institutional quality except governmental stability. Financial development, however, exerts nonlinear effects on income inequality, and the nonlinear effects are heterogeneous between developed (a U-shaped curve) and developing countries (an inverted Ushaped curve). Second, there exists a significant substitutional effect between financial development and each of the aspects of institutional quality in terms of reducing income inequality. Third and last, income inequality exhibits both a direct deteriorating effect and an indirect negative effect on institutional quality through reducing democratic accountability. The findings suggest that improving the existing financial and institutional framework could be an alternative policy vehicle to reduce income inequality, on top of the conventional fiscal tools. Keywords: Income Inequality, Financial Development, Institutional Quality, System GMM